KAJIAN BAURAN PEMASARAN DAN MANAJEMEN PENGETAHUAN DALAM INOVASI KABUTO INSTAN - Sarinah Sarinah; M. Syamsul Maarif; Yandra Arkeman (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2013)
Kabuto instant is a product innovation of cassava flour is dried after fermentation originSoutheast Sulawesi. New product Kabuto instant need to touch the marketing mix and knowledgemanagement (KM) in order to have a competitive edge. The concept of the marketing mix (4P) andKM, both focus on how attempts were made to support the business activities of Kabuto instantproducts to gain a competitive edge. Focus on managing the marketing mix marketing in 4 elements:(1) Product, (2) Promotion, (3) Place, and (4) Price. Management of the marketing mix will increasethe interest of consumers against products Kabuto instant. KM see the knowledge available to abusiness Kabuto instant as a major factor of success. Through knowledge of the company superiorresults can be achieved faster, cheaper and with higher quality than their competitors.Knowledge about customers, target market and other factors that may influence the likelihoodthat a faster utilization of opportunities and a more flexible response to the threat. From theperspective of a marketing mix and KM promising positive impact on the cost structure and revenuestream Kabuto instant. This paper demonstrates the advantages of using the marketing mix and theKM approach that can increase and reduce the risk of business failure by integrating bothapproaches. Management of the marketing mix requires knowledge to manage consumers, consumerknowledge and knowledge of the consumer. KM took on the role as a service provider for theconsumer, managing four (4P) in product innovation Kabuto instant. This study is based on literaturestudies.